The Relationship between Sanitation and Personal Hygiene with Seroprevalence of Toxoplasmosis in Pregnant Women at Kaliwates and Banjarsengon Community Health Centers - Nabila Putri Anissa; Yunita Armiyanti; Eny Nurmaida; Bagus Hermansyah; Erma Sulistyaningsih; Wiwien Sugih Utami (Journal of Agromedicine and Medical Sciences, 2025)
Toxoplasmosis is an infectious disease in animals that can be transmitted to humans. Sanitation and personal hygiene are risk factors for toxoplasmosis. Toxoplasmosis can be transmitted from pregnant women to their fetuses. Toxoplasmosis in pregnancy can cause pregnancy, premature birth, and congenital toxoplasmosis. According to the Jember District Health Office in 2023, access to proper sanitation and good hygienic behavior is still low. The purpose of this study was to analyze the relationship between sanitation and individual hygiene with toxoplasmosis seroprevalence in pregnant women at the Kaliwates and Banjarsengon Health Centers. This study used a crosssectional study type. The subjects of the study were 65 pregnant women at the Kaliwates and Banjarsengon Health Centers who were taken using the accidental sampling technique. The serological examination used the Toxoplasma IgM and IgG ELISA kit from Calbiotech®. The results of this study showed that 77% of pregnantwomen were detected positive for toxoplasmosis. The majority of pregnant women have good sanitation and personal hygiene categories of 87.7% and 90.8%, respectively. Based on the results of Fisher's exact test, sanitation and personal hygiene are not related to toxoplasmosis seroprevalence (p>0.05). This study concludes that sanitation and personal hygiene of pregnant women at the Kaliwates and Banjarsengon Health Centers are not significantly related to toxoplasmosis seroprevalence.